Associations between parental psychological well-being and socio-emotional development in 5-year-old preterm children - Huhtala, Mira; Korja, Riikka; Lehtonen, Liisa; Haataja, Leena; Lapinleimu, Helena; Rautava, Päivi (Early human development, 2014)
Preterm children are at risk for developing behavioral and emotional problems, as well as being less socially competent. Premature birth causes chronic distress in the parents. The aim of the paper is to discover whether parental psychological well-being is associated with the social, behavioral, and functional development of very low birth weight (VLBW, ≤1500g) children at 5years of age. A longitudinal prospective cohort study. A cohort of 201 VLBW infants (≤1500g, <37weeks of gestation) born during 2001–2006 in Turku University Hospital, Finland was studied. At 4-year chronological age of their child, parents independently completed validated questionnaires (Beck Depression Inventory, Parenting Stress Index and Sense of Coherence Scale). At 5years, parents and day-care providers evaluated the development of the child by completing the Five to Fifteen questionnaire. The parents of VLBW children reported significantly more problems in child development compared to the Finnish normative data. Depressive symptoms and weaker sense of coherence in mothers, but not in fathers, were associated with more problems in child development. Parenting stress, for both mothers and fathers, was associated with developmental problems in their child at 5years of age. Maternal depressive symptoms and parenting stress of both parents may be risk factors for the social, behavioral, and functional development of 5-year-old preterm children. On the other hand, stronger maternal sense of coherence may be a protective factor.